Movements, habitat selection and population structure of buffalo (Syncerus caffer caffer Sparrman) in the Sabi Sand Wildtuin - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1992.